HONEYPOT: Intrusion Detection System - Akshay, Akshat Divya; Bhushan, Anchit; Anand, Nihal; Khemka, Rishabh; Devi K. A, Sumithra (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2020)
The number of computers connecting to the internet is getting increased day by day, while the number of computers connected is increasing then it is obvious that the amount of network-based attacks will also increase. In this way, we use a honeypot that is a framework trap that is set to act against unapproved utilization of PCs and data frameworks. Around the globe, a huge number of individuals get to the web each day, honeypot which can likewise be called Intrusion Detection Technology is another time of security innovation that screens device to avoid malicious sports. The whole factor of this research paper is an Intrusion Detection System and Intrusion Prevention System, elements accomplished via honeypot and honeytrap methodologies. A great deal of research went into this review paper and the discoveries propose that the honeypots are drawing in light of a legitimate concern for analysts as a significant security system that can be actualized to stop or occupy the assaults the system assaults and give a chance to find out increasingly more about the source and nature of these assaults. Hence we can say that a honeypot can be utilized as an examination apparatus to accumulate increasingly more data about the expanding number of system assaults that are going on consistently.